2005
DOI: 10.1523/jneurosci.4342-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Exploration-InducedArcmRNA and Protein Expression: Evidence for Selective, Network-Specific Reactivation

Abstract: The immediate-early gene Arc is transcribed in neurons that are part of stable neural networks activated during spatial exploratory behaviors. Arc protein has been demonstrated to regulate AMPA-type glutamate receptor trafficking by recruiting endosomal pathways, suggesting a direct role in synaptic plasticity. The purpose of the present study is to examine the fidelity of Arc mRNA translation and the temporal dynamics of behaviorally induced Arc protein expression after rats explore a novel environment. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

45
310
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(358 citation statements)
references
References 48 publications
45
310
3
Order By: Relevance
“…Messaoudi et al (11) reported that Arc protein synthesis was required for BDNF-induced LTP. Furthermore, two waves of Arc induction have been observed after a single spatial exploration (19). We previously demonstrated that the robust stimulation of TrkB with BDNF in cultured rat cortical cells induced the biphasic expression of Bdnf mRNA, which was observed 1-3 h (primary induction) and 24 -72 h (secondary induction) after the stimulation, and that this biphasic expression of Bdnf mRNA was accompanied by a similar expression profile for Arc mRNA (43).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Messaoudi et al (11) reported that Arc protein synthesis was required for BDNF-induced LTP. Furthermore, two waves of Arc induction have been observed after a single spatial exploration (19). We previously demonstrated that the robust stimulation of TrkB with BDNF in cultured rat cortical cells induced the biphasic expression of Bdnf mRNA, which was observed 1-3 h (primary induction) and 24 -72 h (secondary induction) after the stimulation, and that this biphasic expression of Bdnf mRNA was accompanied by a similar expression profile for Arc mRNA (43).…”
Section: Discussionmentioning
confidence: 92%
“…It is important to note that the induction of Arc mRNA in the secondary phase was mediated by the binding of endogenously synthesized BDNF to TrkB, while the secondary induction of Bdnf mRNA was controlled in an activity-dependent manner (43). Therefore, the distinct usage of the SARE and the proximal Arc promoter may be involved in the control of two waves of Arc induction (19); the secondary wave of Arc synthesis could be mainly mediated by the interaction between secreted BDNF and TrkB under cellular conditions in which HDAC1-mediated repressive activity may have been released from the Arc promoter. Thus, BDNF-induced Arc expression could provide a clearer understanding of the molecular mechanisms underlying Arc-mediated long-lasting changes in neuronal functions in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Messenger RNA (mRNA) levels of the AP-1 transcription factor c-Fos are used as an early measure of altered neuronal metabolic activity (Finkbeiner and Greenberg 1998;Herdegen and Leah 1998). Like c-fos, detection of the immediate early gene arc can be used to indirectly assess levels of neuronal activity (Guzowski et al 2001;Ramirez-Amaya et al 2005). Unlike the transcription factor c-Fos, Arc mRNA and protein are targeted to activate dendrites in an N-methyl-D-aspartate (NMDA) receptor-dependent manner and Arc protein presumably exerts effects on postsynaptic electrophysiological properties through its interaction with the endocytic machinery trafficking alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) receptors (Fujimoto et al 2004;Steward and Worley 2001).…”
mentioning
confidence: 99%
“…One commonality to the gene expression changes found in the present study is their relation to synaptic plasticity. ARC induction, in particular, has been implicated in the formation and strengthening of synaptic formation after NMDA receptor stimulation and learned behavior (Lyford et al, 1995;Guzowski et al, 2001;Steward and Worley, 2001;Ramirez-Amaya et al, 2005). In addition, NGFI-A (egr1, zif/268; (Cole et al, 1989;Wisden et al, 1990)) has been implicated in synaptic formation and learning (Wang et al, 1994;Wang et al, 1995), although it may not be as closely linked as ARC (Guzowski et al, 2001).…”
Section: Discussionmentioning
confidence: 99%